2023
DOI: 10.1038/s41598-023-38262-y
|View full text |Cite
|
Sign up to set email alerts
|

Soft molecularly imprinted nanoparticles with simultaneous lossy mode and surface plasmon multi-resonances for femtomolar sensing of serum transferrin protein

Abstract: The simultaneous interrogation of both lossy mode (LMR) and surface plasmon (SPR) resonances was herein exploited for the first time to devise a sensor in combination with soft molecularly imprinting of nanoparticles (nanoMIPs), specifically entailed of the selectivity towards the protein biomarker human serum transferrin (HTR). Two distinct metal-oxide bilayers, i.e. TiO2–ZrO2 and ZrO2–TiO2, were used in the SPR–LMR sensing platforms. The responses to binding of the target protein HTR of both sensing configur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…From the above figure, it is possible to observe that the LMR resonance wavelength decreases (blue shift) at increasing HTR concentrations. This blue shift is a well-known phenomenon when dealing with nanoMIPs since it was extensively demonstrated that the analyte-nanoMIPs interaction causes a shrinkage of the nanoparticles, reducing the measured refractive index at the sensitive surface [ 22 , 23 , 24 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the above figure, it is possible to observe that the LMR resonance wavelength decreases (blue shift) at increasing HTR concentrations. This blue shift is a well-known phenomenon when dealing with nanoMIPs since it was extensively demonstrated that the analyte-nanoMIPs interaction causes a shrinkage of the nanoparticles, reducing the measured refractive index at the sensitive surface [ 22 , 23 , 24 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this method, it was possible to observe a multi-resonance phenomenon due to the simultaneous excitation of SPR and LMR [ 20 ]. These sensing platforms were recently coupled to molecularly imprinted nanoparticles (nanoMIPs) to conduct binding tests, comparing the obtained performance with the state-of-the-art SPR and LMR biochemical sensors [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations